2017
DOI: 10.1007/s40262-016-0503-3
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Kinase Inhibitors and Proton Pump Inhibitors: An Evaluation of Treatment Options

Abstract: Tyrosine kinase inhibitors (TKIs) have rapidly become an established factor in oncology, and have been shown to be effective in a wide variety of solid and hematologic malignancies. Use of the oral administration route of TKIs offers flexibility and is convenient for the patient; however, despite these advantages, the oral route of administration also causes a highly relevant new problem. Acid-inhibitory drugs, such as proton pump inhibitors (PPIs), increase the intragastric pH, which may subsequently decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 27 publications
0
66
0
Order By: Relevance
“…Alternative strategies that were not implemented at our institution include that of changing twice‐daily PPI regimens to once‐daily regimens, scheduling the PPI to be taken at the same time or 2 hours after the TKI, and adding acidic beverages to overcome this pharmacokinetic drug interaction. Van Leeuwen et al .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Alternative strategies that were not implemented at our institution include that of changing twice‐daily PPI regimens to once‐daily regimens, scheduling the PPI to be taken at the same time or 2 hours after the TKI, and adding acidic beverages to overcome this pharmacokinetic drug interaction. Van Leeuwen et al .…”
Section: Discussionmentioning
confidence: 99%
“…Alternative strategies that were not implemented at our institution include that of changing twice-daily PPI regimens to once-daily regimens, scheduling the PPI to be taken at the same time or 2 hours after the TKI, 7 and adding acidic beverages to overcome this pharmacokinetic drug interaction. Van Leeuwen et al 13 reported that in patients with nonsmall cell lung cancer who took erlotinib with the beverage cola while on esomeprazole, administering erlotinib with cola led to increased erlotinib bioavailability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A PPI‐induced increase in gastric pH has been shown to affect the pharmacokinetics and clinical efficacy of drugs such as tyrosine kinase inhibitors (e.g. ceritinib, dasatinib, erlotinib, gefitinib, lapatinib, nilotinib and pazopanib) and mycophenolate mofetil in transplant recipients . Patients on prolonged treatment with PPIs are at increased risk of severe hypomagnesaemia that sometimes requires hospitalisation .…”
Section: Introductionmentioning
confidence: 99%